APLIKASI MODEL OHLSON PADA SUB SEKTOR LOGAM DAN SEJENISNYA DI INDONESIA - Irawan, Sopyan; Purnamasari, Imas; Tanuatmodjo, Heraeni (Journal of Business Management Education (JBME), 2017)
Objective – To analyze the predictions of bankruptcy of sub-sector of metal and allied companies listed on the Indonesia Stock Exchange in 2010-2015.Design/methodology/approach – This type of research is descriptive method with a total sample of 12 metal and allied sub-sector companies listed on the Indonesian Stock Exchange. The analysis technique used is bankruptcy prediction Ohlson's model (1980). The design of this research is the method of time series design with a period of research for 6 years.Findings – Based on the research results Ohlson models can be used to analyze the bankruptcy of the metal and allied sub-sector companies..Originality/value – The difference in this study lies in the object of research, study time, measuring tools, literature used, the theory used and the results of research. Keywords: Financial Performance, Financial Distress, Bankruptcy, Ohlson’s Model.Type Article: Research paper